Modelagem matemática e simulação numérica de escoamentos incompressíveis sobre geometrias complexas tridimensionais utilizando o método da fronteira imersa - Vedovoto, João Marcelo (2007)
The necessity of understand the physical mechanisms in flows over complexes geometries are something imperative on modern engineering. In this way, tools that allow the analysis and understanding of such flows are very important as well. In this work, a numerical tool that allows the transient analysis of flows over several types of complexes three-dimensional geometries is presented: the Fluids-3D code. Such code uses the Immersed Boundary Method for representing an immersed body into the flow. The Immersed Boundary method uses two independent domains in the solution of the flows over complex geometries: an eulerian domain, which is discretized using Finite Volume Method over a non-uniform mesh to integrate the Navier-Stokes equations, and a second-order approximation for time and space derivatives; the lagrangian domain is represented by a superficial unstructured mesh, composed by triangles. Such mesh can be imported by commercial mesh generators, or generators of files used in stereolithography (*.stl - Standard Tessellation Language). In the Immersed Boundary Method, the effects of an immersed body are imposed by a source term in the Navier-Stokes equations. In this work the Virtual Physical Model for modeling this term is used. Such model is in development in LTCM Laboratory of Heat and Mass Transfer and Fluid Dynamics. The Fluids- 3D code also counts with parallel processing capabilities. The results of flows over several kinds of complexes geometries, such as wall mounted cubes, automobile and aircraft prototypes are shown. These simulations have provided rich analysis of the flows. Others important contributions of the present work are the preparations of the code to the implementation of a graphical user interface, and the optimization of the parallelization process of the code as well.